Entering the House of Celebration: The Missing Fifth Act of Volf's Concept of Embrace. Issue 4 (1st October 2016) - McNeish, David G.
Abstract : The theological concept of embrace, developed by Volf in Exclusion and Embrace (1996), draws heavily on the Parable of the Prodigal Son (Luke 15:11-32). Yet Volf's use of the parable leaves the son at the threshold of his father's house, with no mention of the significance or relevance of the celebration that takes place within the house when the son returns. This article considers the development of Volf's concept of embrace and the four elements he considers essential to the concept. It then proposes that Volf's appeal for reconciliation does not reach as far as either the Parable or our presently unreconciled world requires. A fifth element, that of celebration, is therefore proposed as a necessary, if provocative final act to the drama of embrace.